Study on factors influencing the edge slope of infrared absorption of CdZnTe crystal. (15th March 2020) - Liang, Shijin; Sun, Shiwen; Zhou, Changhe; Xu, Chao; Min, Jiahua; Liang, Xiaoyan; Zhang, Jijun; Jin, Chengwei; Shi, Haozhi; Wang, Linjun; Shen, Yue
Abstract: When the composition of some P-type Cd0.96 Zn0.04 Te (CZT) crystals grown by the vertical Bridgman method (VB) is analyzed by component mapping spectrometer. It is observed that the short-wave (800–1000 nm) infrared absorption edge is inclined, accompanied by a decreased long-wave (400-4000 cm −1 ) infrared transmittance, which leads to an apparent interference of Zn component mapping measurement. In our research, effects of roughness, surface composition, and internal defects on the absorption edge slope of CZT (hereinafter referred to as the edge slope) were investigated by AFM, EDX, XPS and PICTS, and the main cause of non-uniformity of the slope mapping was obtained from annealing treatment. The results indicated that compared with the surface roughness and surface composition due to our surface treatment process, the dominant defect (Cd vacancy) in CZT was the principal influence factor for the edge slope, whose value was negatively correlated with the defect concentration. Furthermore, the inclination of the edge slope and the simultaneous decrease of long-wave infrared transmittance could be respectively explained by the tail state effect and the free carrier absorption caused by high-concentration Cd vacancy absorption. The mapping distribution trend of the slope presented consistency with that of the long-wave transmittance. In addition, the non-uniformity distribution of the edge slope mapping, can be effectively improved by adequate annealing under Cd atmosphere. Steep slopes and a monotonous distribution of Zn content was observed after annealing. Highlights: VCd in P-Cd0.96 Zn0.04 Te was principal factor influencing edge slope, which was negatively correlated with VCd concentration. Slope tilt and transmittance drop were explained by tail state effect and free carrier absorption caused by VCd absorption. The mapping distribution of the edge slope presented consistency with that of the long-wave transmission. The non-uniformity mapping distribution of edge slope can be improved by adequate annealing under Cd atmosphere. Steep slopes and uniformity-distribution slope mapping avoided the measurement interference of Zn component induced by VCd .